Book Review of "The Myth of the Nuclear Revolution: Power Politics in the Atomic Age" by Kier A. Lieber and Daryl G. Press - Natasha McKamey (International Journal of Nuclear Security, 2021)
The Myth of Nuclear Revolution: Power Politics in the Atomic Age is co-written by Keir Lieber and Daryl Press. The authors assess what they refer to as the “central puzzle” of the nuclear age as it currently stands: “the intensity of competition in an era in which victory seemed impossible” (29). They analyze why geopolitical competition persists despite the deterrence developed by the creation and evolution of nuclear weapons. This book aims to solve the Nuclear Puzzle: “if nuclear weapons are such powerful instruments of deterrence then why do so many aspects of international competition in the nuclear age resemble those of the prenuclear era? Why do nuclear powers continue to fear rising powers, strive for superior weaponry, build entangling allies, and covet strategically advantageous territory? If nuclear-armed countries are fundamentally secure from attack, why don’t they act like it?” (120).